Clinical phenotypes of obstructive airway diseases in an outpatient population. (25th November 2016) - Rootmensen, Geert; van Keimpema, Anton; Zwinderman, Aeilko; Sterk, Peter
Abstract: Background and Objectives : Historically, obstructive airway diseases such as asthma and COPD are classified as different diseases. Although the definitions are clearly described, classification of patients into these traditional, clinical disease entity can be difficult. Recent evidence that there are complex, overlapping phenotypes of obstructive lung disease. Our aim was to capture clinical phenotypes of obstructive diseases through the use of cluster analysis in a representative patient population at a common Dutch pulmonary outpatient clinic. Clinical physiological and cellular/ molecular markers were used in the analysis. Methods : To carry out the cluster analysis, an imputed dataset was created from a random sample of 191 adult patients chosen from a pulmonary outpatient clinic. The selection criteria from the sample included patients with a doctor's diagnosis for asthma or COPD. Detailed assessment of patient pulmonary function, blood eosinophil counts, allergic sensitisation and smoking history was collected. Results : We observed four distinct clusters with different clinical characteristics of obstructive lung diseases. Cluster 1: patients with a history of extensive cigarette smoking, airway obstruction without signs of emphysema; cluster 2: patients with features of the emphysematous type of COPD; cluster 3: patients with characteristics of allergic asthma; cluster 4: patients with features suggesting an overlap syndrome of atopic asthma and COPD. Conclusion : Four phenotypes of obstructive lung disease were identified amongst patients clinically labelled as asthma or COPD. These findings emphasize the concept that there are different phenotypes of obstructive lung diseases, including overlapping and complementary disease entities. These phenotypes of chronic airways disease can serve to tailor disease management.